The uncivil side of civil society : the case of BERSIH in Malaysia - Muhamad Takiyuddin Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Coalition for Clean and Fair Elections (BERSIH), often reputed as the champion for electoral reform in Malaysia, has been closely observed by scholars since its inception in 2006. There is a general consensus on the vital role played by BERSIH in fostering the growth of civil society in Malaysia. This article however contends that BERSIH’s establishment as well as its activities and orientation emerge from, and are a reflection of, a specific position within the Malaysian civil society acting as oppositional forces for the Barisan Nasional regime. Rather than uncritically idealizing BERSIH as an embodiment of civil society, this article shed lights on the uncivil side of BERSIH. Using secondary sources and strengthened by interviews with eleven interviewees, this study found that in most cases and under the pretext of civil society, BERSIH is driven by political considerations and applies a narrow interpretation of grassroots democratization. By focussing on its role as domestic election monitoring organization (DEMO), BERSIH’s reputation appears to be in conflict with the prerequisites laid out in the operation of non-partisan DEMOs. Post-2018 General Election saw BERSIH attempting to reposition itself in the new power structure under Pakatan Harapan, at the expense of compromising its principles. The findings of this study also demonstrated the uncivil side of civil society movement such as BERSIH. Applying the term of uncivil society as the exclusive ownership of Malay-Muslim NGOs is misleading and contributes to the misconception that pro-democracy civil society has greater moral clarity.